Atomic–Antarctic terminal zone. Issue 4 (2nd April 2020) - Collignon, Fabienne
ABSTRACT: This article is concerned with the emergence of proto-cybernetic gadgets and specimen in Antarctica. The essay's starting point is that the Cold War was literalised at the South Pole, which also operates as a shadowy double of the overtly militarised Arctic. What happens in Antarctica is a secret assimilation of space into the American Cold War perimeter by way of weapons technology, most notably through the gyrocompass (which develops into the black box navigation systems for ballistic missiles) and the man–machine amalgamation. This assimilation and emergence are traced at hand of exploration narratives (Harold Ponting; Douglas Mawson; Richard Byrd) as well as science fiction stories (H. P. Lovecraft; John W. Campbell, Jr.) that precede the Cold War, but whose forging of a superman-specimen anticipate the conceptualisation of Antarctica as a Cold War space. The South Pole operates as zone of rehearsal for superpower merging: the explorers become prototype cyborgs whose expeditions point towards the containment culture, epitomised in the gyrocompass/black box technology, of the Cold War.